DIFFERENCE IN THE OUTCOME OF PATIENTS MANAGED WITH ISOLATED RENAL INJURY AND CO-EXISTENT ABDOMINAL ORGAN INJURY - Noor, M. Amjad; Ather, M. Hammad (Journal of Ayub Medical College Abbottabad, 2003)
Objective: Involvement of associated intra-abdominal organs like spleen; pancreas, bowel and liver with renal injuries have a higher rate of open operative management. This is often done to avert the potential of peri-renal infection and subsequent risk of secondary hemorrhage of the injured kidney after intra-abdominal surgery. With this background we reviewed our experience to see if operative intervention for co-existing injuries to intra-abdominal organs increase the rate of nephrectomy for grade II-IV renal injuries. Methods: In the period between January 1990 and December 2000, we identified 50 patients managed in this hospital with evidence of external injury resulting in renal trauma. Patients were divided into two groups; i) Patients with isolated renal injury (group A) and ii) renal injury associated with solid abdominal organ injury (group B). The two groups were compared. The severity of renal injury was classified by using the renal injury scale (I-V), which was published by the Organ Injury Scaling (O.I.S.) Committee of the American Association for the Surgery of Trauma (A.A.S.T.) in 19891. Results: Sixty percent patients had associated organ involvement. Penetrating injuries were responsible for 47% patients in-group B compared to only 5% in group A (p<0.001). CT was the predominant radiological investigation in both groups. Spleen was the commonest intra-abdominal organ involved (70%). Mean grade of injury in group-A was 2.2 compared to 2.7 in group B. Operative management was done in 20% patients in group A compared to 29% in group B. Nephrectomy in both groups were performed only for grade V injuries. Conclusions: Exploration does not increase the rate of nephrectomy; in group B grade II-IV injuries when explored were all reconstructed. Penetrating injuries are more likely to cause associated organ injuries (p<0.001). Spleen is the commonest organ involved. Key words: kidney, trauma, intra-abdominal organ, conservative, nephrectomy